2013
DOI: 10.1155/2013/605847
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Water Sorption and Solubility of Dental Adhesive Systems after Cigarette Smoke

Abstract: Aim. To evaluate the effect of cigarette smoke on water sorption and solubility of four adhesive systems. Materials and Methods. Sixteen disks of each adhesive system were prepared (Adper Scotchbond Multipurpose Adhesive (SA); Adper Scotchbond Multipurpose Adhesive System (Adhesive + Primer) (SAP); Adper Single Bond Plus (SB); Adper Easy One (EO)). Specimens were desiccated until a constant mass was obtained and divided into two groups (n = 8). One-half of the specimens were immersed in deionized water, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In this study, the exposure to cigarette smoke was also able to increase the surface roughness and staining of composite resin, in agreement with other studies that have shown the smoke can influence on chemical and mechanical properties of resinous materials 13,17,25,30 .The surface roughness showed by the composite resin exposed to cigarette smoke did not differ from other groups, regardless of the presence of SBAP. The roughness changes of resin exposed to smoke can be attributed to combustion process of organic matter present in tobacco, resulting in presence of carbon monoxide and carbon dioxide, among other harmful substances besides the increase of temperature 13,31 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, the exposure to cigarette smoke was also able to increase the surface roughness and staining of composite resin, in agreement with other studies that have shown the smoke can influence on chemical and mechanical properties of resinous materials 13,17,25,30 .The surface roughness showed by the composite resin exposed to cigarette smoke did not differ from other groups, regardless of the presence of SBAP. The roughness changes of resin exposed to smoke can be attributed to combustion process of organic matter present in tobacco, resulting in presence of carbon monoxide and carbon dioxide, among other harmful substances besides the increase of temperature 13,31 .…”
Section: Discussionsupporting
confidence: 91%
“…The roughness changes of resin exposed to smoke can be attributed to combustion process of organic matter present in tobacco, resulting in presence of carbon monoxide and carbon dioxide, among other harmful substances besides the increase of temperature 13,31 . Furthermore, an acidic pH solution can be produced by mixing water contained in saliva and cigarette components as carbon dioxide, promoting damage to resin surface integrity 32 .These factors can compromise the organic matrix stability, causing superficial degradation of material.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Vitoria et al 21 demonstrated that cigarette smoke enhances the diffusion dynamics of adhesive system liquids by reducing their physical properties.…”
Section: Discussionmentioning
confidence: 99%